EFEKTIFITAS EKSTRAK BAWANG MERAH TERHADAP PERTUMBUHAN BENIH STROBERI (fragaria chiloensis L.) - Apriyansyah, Jaka; Haryuni; Risky; Eko Fransisko (PUCUK : Jurnal Ilmu Tanaman, 2023)
One effort made by farmers to increase the production of strawberry plants is by using external seeds, for example, California and Mencir. The use of these seeds is a difficult thing because these seeds are quite expensive and difficult to obtain, although these seeds can produce high productivity but can also have a negative impact on the resistance of these seeds, so for strawberry cultivation you can use growth regulators (ZPT).The use of growth regulators is one of the efforts that can be made to increase plant growth. There are two types of growth regulators, namely natural growth regulators and synthetic (artificial) growth regulators. Natural growth regulators have more economic value, because these growth regulators are easier on the environment than artificial growth regulators (Tana and Bumbungan, 2017). The method used in this study was a completely randomized design (CRD) and the treatment was shallot extract(Allium cepa L.)which consisted of 6 levels with 3 repetitions and each repetition consisted of 5 samples, with doses of K0 = 0ml/100ml, K1 = 20ml/100ml, 40ml/100ml, 80ml/100ml, and 100ml/100ml of water. The number of plants in the study was P x T x U = 6 x 5 x 3 = 90 plants. The onion extract treatment had different results. It is known that the treatment with the concentration of onion extract ml/100ml of water) which gave the highest yield on the growth percentage variable, namely 93.3%. then all treatments of red onion extract concentrations gave the same average on the variables when shoots appeared, namely 7 daysGrowth of shoots on strawberry plants andat concentrations of 20ml/100ml, 40ml/100ml, 60ml/100ml, 80ml/100ml, and 100ml/100ml growth in plant height increased, then on the variable number of leaves with K1 concentration (20ml/100ml water) the average number of leaves was 3 to 4 strands at a concentration of shallot extract 20%/100ml. So it can be concluded that there is a significant effect on the application of shallot extract in the growing percentage of strawberry plants and the most effective dose in the growing percentage of strawberry plants is K2.